CCD photometric investigation of a W UMa-Type binary GSC 0763-0572 - Wichean Kriwattanawong (2018)
A photometric solution of an A-type W UMa binary, GSC 0763-0572, is examined with a revised orbital period. The overcontact degree is found to be f = 40.66%, with a low mass ratio of q = 0.2554. The result demonstrates an unambiguous increase in the orbital period with a relative period change of ΔP/P = +5.69 × 10-7d yr-1. This indicates that GSC 0763-0572 is undergoing a process of mass transfer from the secondary component to the primary one with a rate of relative mass change of Δm1/m = +5.18 × 10-8yr-1, for a conservative model of mass transfer. We find that GSC 0763-0572 might transform into a rapidly rotating star, if total spin angular momentum increases until it is greater than one-third of the orbital angular momentum, without breaking the contact configuration. © 2012 National Astronomical Observatories of Chinese Academy of Sciences and IOP Publishing Ltd.